Interplay between nano zinc oxide-coated urea and summer green manuring in basmati rice under basmati rice-wheat cropping system: implications on yield response, nutrient acquisition and grain fortification - Baral, Kirttiranjan; Shivay, Yashbir Singh; Prasanna, Radha; Kumar, Dinesh; Shrivastava, Manoj; Chakraborty, Debashis; Kumar, Rajesh; Srinivasarao, Cherukumalli; Mandi, Sunil; Nayak, Somanath; Reddy, Kadapa Sreenivasa; Yashavanth, B. S. (Frontiers in Sustainable Food Systems, 2023)
Identifying appropriate nutrient management options is crucial for reversing the yield plateau and enhancing the nutritional status of basmati rice under the basmati rice-wheat cropping system of the Indo Gangetic plain (IGP). Alternative to the conventional chemical fertilizer, ZnO nanoparticles as carrier material for the micronutrient Zn has shown promise in reducing the bulkiness of fertilizer use in the soil-plant environment. But whether its integration and interaction with an organic source such as green manuring could enrich basmati rice grain with micronutrients and promote protein nutrition is not well investigated. Therefore, we conducted a field experiment in split-plot design for two consecutive kharif seasons with two summer green manuring options (Sesbania and cowpea, along with fallow) as main plots and six fertilization strategies as subplots (5 kg Zn ha–1 as bulk ZnO, N at 120 kg N ha–1 as prilled urea (PU), N at 120 kg N ha–1 as PU + 5 kg ha–1 as bulk ZnO, 1% bulk ZnO-coated PU, 0.1% nano ZnO coated PU and 0.2% nano ZnO coated PU replicated thrice. Our findings revealed that with the application of 1% Bulk ZnO coated PU with Sesbania; the yield response, micronutrient acquisition, and protein accumulation in milled rice was higher than in other plant fertilization methods. However, in plots treated with Sesbania, the plants treated with 0.2% nano ZnO-coated PU exhibited statistically equivalent yield and micronutrient loading in edible tissues. Hence, this study unveils the critical role of nano ZnO-coated urea and summer green manuring in elevating micronutrient and protein bioavailability in basmati rice and concurrently reducing Zn dose by 20%, making it a profitable option for farmers.